Ecosystem Services and Stakeholder Analysis in Bishajari Lake and Associated Wetland Areas, Chitwan, Nepal - Khanal, S.; Gurung, S. B.; Pant, K. K.; Chaudhary, P.; Dangol, D.R. (International Journal of Applied Sciences and Biotechnology, 2014)
Wetlands as other ecosystems deliver goods and services of enormous value to the human society and are regarded as one of the most productive ecosystems. We assessed the ecosystem services delivered by Bishajari Lake and its associated wetland areas of Chitwan district during June to August, 2012. A household survey consisting 110 households, interviews with key informants, group discussions and stakeholder analysis were carried out for this purpose to document the overall status of ecosystem services, evaluate the provisional services generated by the lakes, understand potentials for payment to ecosystem services, and identify stakeholders involved and their roles and responsibilities. A total of 12 fish species, 17 wild and domestic fruits, 12 timber species, 15 fodder species, 20 wild vegetables species and 31 medicinal plant species were recorded. Moreover 65.5% of respondents were found receiving some sort of income from the wetland area. The majority of respondents felt that the ecosystem is being changed mostly on provisional services. So far with little support from government, the local people have practiced some adaptive responses like biogas plant, afforestation, electric fencing, contract fisheries, ecotourism and other climate-smart measures. It suggest that raising awareness and sharing information among the locals should be done more frequently and effectively to continuously cope with ecosystem change. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11552  Int J Appl Sci Biotechnol, Vol. 2(4): 563-569